2018
DOI: 10.1016/j.nrjag.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural study using 2D modeling of the potential field data and GIS technique in Sohag Governorate and its surroundings, Upper Egypt

Abstract: The main purpose of the present study is to identify the surface and subsurface structural features and configuration of the basement in the area around Sohag Governorate using Geographic Information System (GIS) and potential field data (gravity and aeromagnetic). The hill shade was found as the most suitable image for surface lineament delineation and to produce a fault potential prediction map using the overlay model technique. The subsurface faults and contacts were detected and traced out from the reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Power spectrum analysis represents one of the most common methods to figure out the depth of gravity sources (Spector and Grant, 1970). The gravity maps' power spectrum is the product of their 2D Fourier transform and complex conjugate (Ghazala et al, 2018). The average depth of the gravity source can be related to specific features in the radially averaged power spectrum.…”
Section: • Power Spectrum Analysismentioning
confidence: 99%
“…Power spectrum analysis represents one of the most common methods to figure out the depth of gravity sources (Spector and Grant, 1970). The gravity maps' power spectrum is the product of their 2D Fourier transform and complex conjugate (Ghazala et al, 2018). The average depth of the gravity source can be related to specific features in the radially averaged power spectrum.…”
Section: • Power Spectrum Analysismentioning
confidence: 99%
“…2 The methodology flowchart. spectrum is the product of their 2D Fourier transform and complex conjugate (Ghazala et al, 2018). According to Equation (1), it is a function of wavelength for both the s and c directions.…”
Section: Power Spectrum Analysismentioning
confidence: 99%
“…The combination of the NW-SE fractures has been explained as conjugated sets due to the compression stress produced in the north-northeast (NNE) direction [35]. The presence of some intrusive bodies of granodiorite rock type in the area of study has been identified [36].…”
Section: Location Geology and Structure Of The Study Areamentioning
confidence: 99%